Effectiveness of learning in online academic courses compared with face‐to‐face courses in higher education - Soffer, Tal; Nachmias, Rafi (Journal of computer assisted learning, 2018)
This study examined the effectiveness of 3 online courses compared with the same 3 courses in a face‐to‐face (F2F) format, which had the same characteristics (e.g., the same instructor and final exam content and place). Effectiveness was examined by utilizing a wide range of variables, including 2 objective measures (N = 968): grades and completion rate; and 9 subjective measures (N = 360): 7 measures include instructional aspects (course structure, learning content, lessons watched, assignments, communication), engagement, and satisfaction. Findings indicate significant differences between online and F2F courses in most of the examined variables. Students in the online courses reported better understanding of the course structure, better communication with the course staff, watching the videos lessens more, and higher engagement and satisfaction. Students in the F2F courses reported better contribution of the learning content. Students' final grades were higher in the online courses, and no differences were found in the completion rate. The findings suggest that in many of the examined effectiveness aspects, online courses are as effective as, or more effective than, F2F courses. Interpretations of the findings are discussed. Lay Description What is currently known about the subject matter? Course effectiveness is defined by students' motivation and satisfaction or their grades. Some studies report more satisfaction and motivation in online courses, rather than face‐to‐face (F2F) courses. Online learning is more or less as effective as F2F learning in regard to grades. What the paper adds to this: Expansion of the term “effectiveness” by measuring it using a large scope of variables. Examination of courses across various disciplines, with a relatively large sample size. Online courses were as effective as, or more than, F2F courses in most variables measured. Differences between the formats relate to the course discipline. Implications of the study findings: Online learning may be a suitable alternative to academic F2F courses. Well‐structured course design should be considered when developing online courses. Content and discipline characteristics should be considered when developing online courses.